Case report: Long response to PD-1 blockade after failure of trastuzumab plus chemotherapy in advanced Epstein-Barr virus-associated gastric cancer - Pan, Yan; Lu, Linbin; Liu, Huan; Chen, Di; Han, Ning; Yao, Ruirong; Wang, Xinlin; Gao, Xianchun; Yu, Jun; Chen, Ling; Zhou, Fenli; Hao, Guangjun; et al. (Frontiers in Immunology, 2022)
Background: Trastuzumab-containing chemotherapy is the first-line treatment for advanced gastric cancer (GC) with HER2 positive. Although PD-1 inhibitors significantly improved the outcome of GC patients refractory to previous chemotherapy regimens, few studies explore the role of anti-PD-1 therapy overcomes resistance to trastuzumab plus chemotherapy in advanced Epstein-Barr Virus-associated gastric cancer(EBVaGC) with PD-L1 and HER2 positive. Case Presentation: We report a case of advanced EBVaGC in a 45-year-old man presenting with fatigue, dysphagia, and weight loss for several months. Initial endoscopy revealed a large tumor at the gastroesophageal junction. Computed tomography revealed GC accompanied by multiple lymph nodes and hepatic and pulmonary metastases. The immunohistochemistry indicated that HER-2 and PD-L1 were overexpressed, and tumor cells were positive for EBV-encoded small RNA (EBER) by in situ hybridization. Trastuzumab plus DCS was started as first-line chemotherapy with a PFS of 4 months and shifted to trastuzumab plus FOLFIRI or gemcitabine as second-/third-line therapy. After five-cycle nivolumab monotherapy, the patient received partial response and was treated with total radical gastrectomy plus sequential radiotherapy. He continued the postoperative immunotherapy over 30 cycles with a PFS of 28 months. Due to a new abdominal lymph node metastasis confirmed by PET-CT, he received toripalimab as next-line treatment and achieved complete remission as the best objective response. Summary: We presented an advanced HER2-positive EBVaGC patient with PD-L1 high expression, refractory to trastuzumab plus chemotherapy, and had a durable clinical benefit sequence with a single dose of the PD-1 inhibitor.